2020
DOI: 10.1002/ppul.25221
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel informational booklet for pediatric long‐term ventilation decision support

Abstract: Objectives To provide accessible, uniform, comprehensive, and balanced information to families deciding whether to initiate long‐term ventilation (LTV) for their child, we sought to develop and validate a novel informational resource. Methods The Ottawa Decision Support Framework was followed. Previous interviews with 44 lay and 15 professional stakeholders and published literature provided content for a booklet. Iterative versions were cognitive tested with six parents facing decisions and five pediatric inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Care should be taken to ensure that content supports parents leaning towards, or against, home ventilation equally. Web‐based decisional tools, 32 online resources, 33 and informational booklets 34 developed with the intention of providing balanced perspectives could help achieve this end. Of course, any standardized approach must be modifiable to the individual family context.…”
Section: Discussionmentioning
confidence: 99%
“…Care should be taken to ensure that content supports parents leaning towards, or against, home ventilation equally. Web‐based decisional tools, 32 online resources, 33 and informational booklets 34 developed with the intention of providing balanced perspectives could help achieve this end. Of course, any standardized approach must be modifiable to the individual family context.…”
Section: Discussionmentioning
confidence: 99%
“…Few decisional tools are available to support family‐caregivers through decision‐making (e.g., booklets, infographics, data visualization, or video testimonies). Only one study measured changes in caregiver decisional conflict scores when an information tool was used, although this did not reach significance 68 . No studies were found analyzing effective strategies to mitigate family‐caregivers' mental stress.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study measured changes in caregiver decisional conflict scores when an information tool was used, although this did not reach significance. 68 No studies were found analyzing effective strategies to mitigate family-caregivers' mental stress.…”
Section: Therapy Goalsmentioning
confidence: 99%
“…Whilst individual neuromuscular and central hypoventilation diagnoses might be rare, the total population of children affected by these conditions is increasing (Rose et al, 2019; Woodcock et al, 2016). Moreover, these children are living longer lives (Barker et al, 2023; Castro‐Codesal et al, 2018; Flotats‐Bastardas & Hahn, 2020; National Confidential Enquiry into Patient Outcome and Death [NCEPOD], 2020; Turner, 2023; Wallis et al, 2011), with associated and changing expectations about the scope of their anticipated life experiences and opportunities (Bayes et al, 2012; Edwards et al, 2021). Understanding the value of expanding opportunities for children requiring nocturnal ventilation to include air travel requires consideration of the clinical implications for the individual child, knowledge of the practical issues and appreciation of the meaning of these ambitions for the child and family.…”
Section: Introductionmentioning
confidence: 99%